Strategies to Increase the Adoption of Residential Pollinator Gardening: Tackling Percieved Barriers - Colby Silvert; Laura A. Warner; John Diaz; Cody Gusto; Rachel Mallinger (EDIS)
Urbanization and development of managed landscapes can harm pollinators by reducing flowers and vegetation and increasing exposure to chemicals. However, research shows that urban, developed landscapes can be designed and maintained to successfully provide habitats for diverse, healthy pollinator populations, including bees. Therefore, a major opportunity and need exist for residents, particularly those living in urban areas, to support bees and other pollinators by adopting pollinator gardening in their landscapes. Based on recent research about significant barriers and solutions, this publication intends to guide Extension agents and other practitioners on how to best encourage and facilitate adoption of pollinator gardening by addressing residents’ perceptions.